Abundant of flies (DIPTERA) in closed and opened house commercial chicken and duck farms in Kinta district, Perak, Malaysia - Navanithakumar Ballakrishnan; Hadura Abu Hasan; Hamdan Ahmad; Hasber Salim (Penerbit Universiti Kebangsaan Malaysia, 2024)
Malaysian commercial poultry production systems are highly integrated with intensive production techniques that result in constant manure accumulation, which supports the development of several serious fly pests. Hence, field sampling was conducted to determine fly distributions in closed and open house commercial chicken and duck farms in Kinta district, Perak, Malaysia. The distribution of dipteran flies was analyzed at 14 commercial poultry farms. A total of 7,993 flies captured belonged to nine families namely Muscidae, Calliphoridae, Sacrophagidae, Ulidiidae, Phoridae, Stratiomyidae, Sciaridae, Fannidae and Syrphidae. Musca domestica was the predominant fly species and it represented 74.12% (open house) and 72.42% (closed house), while Megaselia scalaris was the second most abundant species constitutes (21.69% in open house and 26.52% in closed house farming system). Physiphora clausa, fungus gnat, Fannia sp., Atherigona orientalis and Lucilia cuprina were only encountered in open house poultry farms. However, the lowest flies’s families were Syrphidae and Sciaridae, constituting only 0.01% of all collected flies in both open and closed house farms.